Dampak Penggunaan AI pada Pola Pembelajaran pada Mahasiswa di Kampus IAIN Fattahul Muluk Papua - Meidiah, Alifia Nida Safira; Saifudin, Muhammad; Yusuf, Muhamad; Zulihi, Zulihi; Watora, Ibrahim (Tapis: Jurnal Penelitian Ilmiah, 2025)
Students, as members of the digital generation, constitute the group that makes the most extensive use of Artificial Intelligence (AI) in academic activities. They employ AI based services to complete various tasks, whether consciously or not. This trend indicates that education is increasingly shifting toward a more autonomous, flexible, and technology-driven learning model. This study aims to examine how the use of AI affects students at IAIN Fattahul Muluk Papua, both in terms of its benefits and its challenges, including its influence on creativity, independent thinking, and academic integrity. The research employs a qualitative descriptive method, with data collected through passive participatory observation, in-depth interviews, and documentation. Data analysis was conducted using an interactive model. The findings reveal that technological advancements, particularly AI, have transformed the ways in which students at IAIN Fattahul Muluk Papua search for information, comprehend learning materials, and complete academic assignments. AI enhances learning efficiency by providing rapid access to references, assisting with idea development, and offering concise information. However, the study also identifies the risks of excessive reliance on AI, which may weaken students’ critical thinking skills, creativity, and independence, as well as increase the potential for plagiarism. Thus, while AI can support the emergence of original ideas when used appropriately, it may also undermine academic abilities when misused. Therefore, digital literacy, ethical AI usage, and educator guidance are essential.